2001
DOI: 10.1098/rspb.2001.1600
|View full text |Cite
|
Sign up to set email alerts
|

Determination of biogeographical range: an application of molecular phylogeography to the European pool frogRana lessonae

Abstract: Understanding how species are constrained within their biogeographical ranges is a central problem in evolutionary ecology. Essential prerequisites for addressing this question include accurate determinations of range borders and of the genetic structures of component populations. Human translocation of organisms to sites outside their natural range is one factor that increasingly complicates this issue. In areas not far beyond presumed natural range margins it can be particularly difficult to determine whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 30 publications
4
72
0
1
Order By: Relevance
“…Interestingly, we detected the highest levels of developmental plasticity in the marginal Swedish pool frog populations, which harbour very low variability in genetic markers (Sj€ ogren 1991;Zeisset and Beebee 2001). These results reinforce the view that the lack of neutral genetic variation may not be a good proxy for estimating the degree of developmental plasticity for a population (Reed and Frankham 2001).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Interestingly, we detected the highest levels of developmental plasticity in the marginal Swedish pool frog populations, which harbour very low variability in genetic markers (Sj€ ogren 1991;Zeisset and Beebee 2001). These results reinforce the view that the lack of neutral genetic variation may not be a good proxy for estimating the degree of developmental plasticity for a population (Reed and Frankham 2001).…”
Section: Discussionsupporting
confidence: 75%
“…1; Table 1): three populations from Poland (centre of the distribution), two from Latvia (edge populations) and three from Sweden (marginal northern populations). The Swedish population is a relic of postglacial migrations, becoming isolated from the main distribution area during the cooling period around 10.000 BP (Zeisset and Beebee 2001). The present Swedish population is isolated by more than 300 km from the closest continental populations located in Estonia (Orizaola et al 2010; Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microsatellite and random amplified polymorphic DNA analyses strongly inferred that some populations of the pool frog R. lessonae in eastern England were native to the country, rather than a recent introduction as previously thought, and are part of a distinct clade only otherwise found in Scandinavia (Zeisset and Beebee, 2001;Snell et al, 2005). A rather unexpected northerly postglacial colonization route westwards from Scandinavia ( Figure 5) may, it turns out, have been followed by other organisms as well (Bunje, 2005;Piertney et al, 2005).…”
Section: Zeisset and Tjc Beebeementioning
confidence: 98%
“…using chloroplast DNA variation concluded that these trees appear to have colonized Britain through France, having followed a route from a refugium in Iberia (Dumolin-Lapegue et al, 1997). Studies on pool frogs (Rana lessonae) show an interesting alternative route into Britain through Poland from a refugium in Italy, based on microsatellite and random amplified polymorphic DNA analyses (Zeisset and Beebee, 2001;Snell et al, 2005). These distinct histories might be explained by differences in the ecology of the species, differences in the refugial origins of the colonizers or by events affecting the rate of expansion from different refuges.…”
Section: Introductionmentioning
confidence: 99%